An Analysis of Translation Procedures Found in the Translation of Movie Subtitle: Zootopia - Fenti Rizki Ananda; Diana Chitra Hasan; Temmy Thamrin (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2019)
In this research, the writer attempts to find out the translation procedures in the translation of movie subtitle: Zootopia from English to Indonesian subtitle to determine the intended audience of the movie. The research used a descriptive qualitative method. The data of this research are the utterances or sentences in movie subtitle both English and Indonesian with the source of the data of this research is Zootopia movie. The writer used Indonesian subtitle from the site called subscene where the translators around the world could translate movies into many languages. The data collected by watching the movie with both English and Indonesian subtitles, and categorized the collected data based on each translation procedures of Newmark. The writer figured out that the intended audience is all ages group and the writer also found ten translation procedures used in the movie subtitle: Zootopia. The ten translation procedures are couplets, modulation, paraphrase, reduction, literal translation, cultural equivalent, transference, functional equivalent, naturalisation, transposition/shifts. Based on the findings, it can be concluded that the intended audience of Zootopia movie is all ages group and there are ten from nineteen procedures are found in the movie subtitle: Zootopia.